Relação entre pressão intracraniana, atenção e coordenação motora fina após inclinação negativa da cabeça em indivíduos saudáveis - Santos, Thainá Cristina Ramos dos (Universidade Federal de São Carlos, 2023)
Man's trip to the moon was one of the most awaited moments for mankind, and we are moving towards the next step: going to Mars. With this in mind, there are several studies on the effects caused by microgravity on the astronaut's body. These changes occur due to the change in the hydrostatic gradient of space in relation to the Earth, so the human body suffers a displacement of fluids in which there is a decrease in hydrostatic pressure in the lower limbs and an increase in the upper limbs, especially in the cranial cavity. Thus, astronauts are susceptible to suffer increased intracranial pressure (ICP), directly impacting the functioning of the Central Nervous System (CNS) and may result in functional deficits, such as difficulty in motor coordination and impairment of cognitive aspects. In monitoring ICP, the invasive method is usually used, which is considered the gold standard, but non-invasive methods have gained importance for the space environment. For the simulation of microgravity there is a widely used form that is the negative head tilt (or head-down tilt), which enables studies of the changes caused by the redirection of fluids in the terrestrial environment. Objective: To relate the morphology of the ICP wave with performance in cognitive and motor tests; to identify changes in performance in the pre- and post-head-down tilt tests. Methodology: 48 healthy, active individuals of both sexes, aged 25-45 years, who fit the eligibility criteria. Blood tests and Cardiopulmonary Exercise Test (CPET) were performed, followed by the experimental protocol. This consisted of two steps: application of the cognitive tests, followed by 30 minutes of negative head tilt at -15°, and repetition of the tests. Then, ICP was monitored for 60 minutes (15 minutes in neutral position, 30 minutes at -15°, and 15 minutes again in neutral position). Statistics: Tests for normality and homogeneity of the data were applied. To evaluate the performance in the pre- and post-maneuver postural tests, paired t test was performed in parametric case and Wilcoxon test in nonparametric case. For the variable P2/P1 ratio, repeated measures ANOVA test was performed comparing the different postures (pre, during, and post-head-down tilt test). Pearson for parametric and Spearman for nonparametric (post test and ICP during HDT) were used for correlation. For all analyses a significance level of 5% and a confidence interval of 95% were considered. Results: No significant differences were observed when comparing the pre and post head-down tilt. Conclusion: Studies with longer durability and different groups should be conducted.
Relationship between intracranial pressure, attention and fine motor coordination after negative head-down tilt in healthy subjects
Keywords: Hipertensão intracraniana; Head-down tilt; Microgravidade; Simulação; Coordenação motora; Sistema nervoso central; Intracranial hypertension; Microgravity; Simulation; Motor coordination; Central nervous system; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL